2020
DOI: 10.1002/app.50306
|View full text |Cite
|
Sign up to set email alerts
|

The fiber‐matrix interface in Ioncell cellulose fiber composites and its implications for the mechanical performance

Abstract: Fiber‐reinforced composites based on natural fibers are promising alternatives for materials made of metal or synthetic polymers. However, the inherent inhomogeneity of natural fibers limits the quality of the respective composites. Man‐made cellulose fibers (MMCFs) prepared from cellulose solutions via wet or dry‐jet wet spinning processes can overcome these limitations. Herein, MMCFs are used to prepare single fiber epoxy composites and UD composites with 20, 30, 40, and 60 wt% fiber loads. The mechanical pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
(62 reference statements)
2
2
0
Order By: Relevance
“…It was observed that as DR increased, fiber diameter decreased, accompanied by respective increases of nearly 25% and 20% in tensile modulus and strength, respectively. These findings are in accordance with an earlier study by the authors, which demonstrates that the orientation of the cellulose chains increases with higher DR s. 33…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…It was observed that as DR increased, fiber diameter decreased, accompanied by respective increases of nearly 25% and 20% in tensile modulus and strength, respectively. These findings are in accordance with an earlier study by the authors, which demonstrates that the orientation of the cellulose chains increases with higher DR s. 33…”
Section: Resultssupporting
confidence: 94%
“…These findings are in accordance with an earlier study by the authors, which demonstrates that the orientation of the cellulose chains increases with higher DRs. 33 In consideration of the fiber geometry, orientation, and VFs mimicking the manufacturing process, the abovementioned random fiber deposition technique was implemented where the untrimmed fiber has a length, l, of 10 mm, average diameter of 14 μm, in-plane orientation θ of 0°, and polar orientation f of 0°, and the matrix has the dimensions of L = 10 mm, W = 0.3 mm, and T = 0.3 mm. The fibers exceeding the matrix boundaries were trimmed, and fiber length distribution after trimming operations was provided for the specimens with VF ¼ f16:7%, 25:5%, 35%, 55%g as seen in Figure 6.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fibers exhibited uniform breakage without evidence of debonding or pull-out, and no instances of adhesion or cohesion failure were observed. This finding aligns with a similar observation reported in prior studies, 48 underscoring the robust compatibility between the matrix and Ioncell fibers, a critical factor influencing mechanical properties. Comparatively, the fracture surface of the viscose fiber composite (VFRC) is presented in Fig.…”
Section: Resultssupporting
confidence: 92%